Biodiversity hotspots and conservation efficiency of a large drainage basin: Distribution patterns of species richness and conservation gaps analysis in the Yangtze River Basin, China. Issue 4 (8th March 2022) - Zhang, Wendi; Bussmann, Rainer W.; Li, Jin; Liu, Bo; Xue, Tiantian; Yang, Xudong; Qin, Fei; Liu, Huiming; Yu, Shengxiang
Abstract: The Yangtze River Basin (YRB), a key biodiversity area and a major economic zone in China, the biodiversity of the area is confronted with severe challenges. In this paper, we analyzed species distribution patterns based on a dataset with 18, 538 seed plant species to identify hotspots and evaluate conservation effectiveness and gaps of the YRB. We calculated distribution patterns of species richness with the top 5% richness algorithm and complementarity algorithm, and reconstructed a phylogenetic tree and elucidated spatial phylogenetics. There were 214 hotspot grid cells covering only 6.8% of the study region, but containing 88% seed plant species. Then, we conducted correlation analysis on distribution patterns of different algorithms and species categories, which showed moderate or weak correlations between the top 5% richness algorithm and complementary algorithm. Conservation effectiveness analysis indicated there were 116 hotspot grid cells (accounting for 73.6% of the total species) protected by current conservation networks and there are many conservation gaps remaining. Finally, we used the maximum entropy model (MaxEnt) to predict suitable habitat areas of threatened species under current and future climate scenarios. Prediction analysis results indicated future expansion of suitable habitat to the southeast, and reduction in the central and western portions of the study area. When we considered anthropogenic areas, the suitable habitat was severely decreased, indicating the importance of optimizing the layout of conservation networks and comprehensive biodiversity conservation planning in the YRB.